North-South Technology Spillovers: The Relative Impact of Openness and Foreign R&D - Schiff, Maurice; Wang, Yanling (2012)
This paper examines the relative contribution of openness and the R&D content of trade to North-South trade-related knowledge diffusion and TFP growth. The measure of foreign R&D used in the literature on trade-related knowledge diffusion imposes identical contributions to TFP of openness and the R&D content of trade. We show that this restriction is not warranted and that openness has a greater impact on TFP than R&D. This finding is particularly strong in low R&D-intensity industries and--as might be expected--not as strong in R&D-intensive ones. The results indicate that the impact of openness on TFP in developing countries is larger than previously obtained in this literature, and that developing countries can obtain larger productivity gains from trade liberalization than previously thought.